Four limit cycles in a predator–prey system of Leslie type with generalized Holling type III functional response. (December 2019) - Dai, Yanfei; Zhao, Yulin; Sang, Bo
Abstract: This paper, as a complement to the works by Hsu et al [SIAM. J. Appl. Math. 55 (1995)] and Huang et al [J. Differential Equations 257 (2014)], aims to examine the Hopf bifurcation and global dynamics of a predator–prey system of Leslie type with generalized Holling type III functional response for the two cases: (A) system has a unique anti-saddle positive equilibrium, which is not semi-hyperbolic or nilpotent; (B) system has three distinct positive equilibria. For each case, the type and stability of each equilibrium, Hopf bifurcation at each weak focus, and the number and distribution of limit cycles in the first quadrant are studied. It is shown that every equilibrium is not a center for all parameter values. For the case (A), i limit cycle(s) can appear near the unique positive equilibrium, i = 1, …, 4 . For i = 3 or 4, system has two stable limit cycles, which gives a positive answer to the open problem proposed by Coleman [Differential equations model, 1983]: finding at least two ecologically stable cycles in any natural (or laboratory) predator–prey or other interacting system. For the case (B), one positive equilibrium is a saddle and the others are both anti-saddle. If one of the two anti-saddles is a weak focus and the other is not, then the order of the weak focus is at most 3. If both anti-saddles are weak foci, then they are unstable weak foci of order one. Moreover, one limit cycle can bifurcate from each of them simultaneously. Numerical simulations demonstrate that there is also a big stable limit cycle enclosing these two limit cycles. Our results indicate that the maximum number of limit cycles in the model of this kind is at least 4, which improves the preceding results that this number is at least 2.